Minimum requirements for the diagnosis of psychogenic nonepileptic seizures: A staged approach: A report from the International League Against Epilepsy Nonepileptic Seizures Task Force. Issue 11 (20th September 2013) - LaFrance, W. Curt; Baker, Gus A.; Duncan, Rod; Goldstein, Laura H.; Reuber, Markus
Summary: An international consensus group of clinician‐researchers in epilepsy, neurology, neuropsychology, and neuropsychiatry collaborated with the aim of developing clear guidance on standards for the diagnosis of psychogenic nonepileptic seizures (PNES). Because the gold standard of video electroencephalography (vEEG) is not available worldwide, or for every patient, the group delineated a staged approach to PNES diagnosis. Using a consensus review of the literature, this group evaluated key diagnostic approaches. These included: history, EEG, ambulatory EEG, vEEG/monitoring, neurophysiologic, neurohumoral, neuroimaging, neuropsychological testing, hypnosis, and conversation analysis. Levels of diagnostic certainty were developed including possible, probable, clinically established, and documented diagnosis, based on the availability of history, witnessed event, and investigations, including vEEG. The aim and hope of this report is to provide greater clarity about the process and certainty of the diagnosis of PNES, with the intent to improve the care for people with epilepsy and nonepileptic seizures.